Resistance of Bacillus subtilis var. niger Spores Occluded in Water-insoluble Crystals to Three Sterilization Agents - Doyle, John E. (1967)
The resistance to destruction of spores of Bacillus subtilis var. niger occluded in crystals of calcium carbonate and exposed to ethylene oxide and moist and dry heat was determined and compared with the destruction of unoccluded spores. Occluded spores could not be inactivated with ethylene oxide. Resistance to inactivation was approximately 900 and 9 times higher for occluded than for unoccluded spores subjected to moist and dry heat, respectively, at 121 C. The protective effect may be due either to the unavailability of oxygen for destruction by oxidation or to inhibition of the loss of essential cell constituents by vaporization. Evidence also implicates the crystal structure as a thermal conductivity barrier. Occluded spores retained viability over a 3-year period compared with unoccluded spores which decreased over 90% during this period. Occluded spores in insoluble materials are seldom encountered in the technology of sterilization, but could be the most critical factor in the sterilization of interplanetary vehicles. Entrapped spores in insoluble materials are usually difficult to detect, and are very stable as well as extremely resistant to destruction by heat and ethylene oxide.